2021
DOI: 10.1038/s41598-020-80857-2
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA methylation mediates the association of male age on reproductive outcomes among couples undergoing infertility treatment

Abstract: Parental age at time of offspring conception is increasing in developed countries. Advanced male age is associated with decreased reproductive success and increased risk of adverse neurodevelopmental outcomes in offspring. Mechanisms for these male age effects remain unclear, but changes in sperm DNA methylation over time is one potential explanation. We assessed genome-wide methylation of sperm DNA from 47 semen samples collected from male participants of couples seeking infertility treatment. We report that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 94 publications
3
32
1
Order By: Relevance
“…The observation is consistent with numerous studies that put into context aberrant sperm quality parameters and changes in mCpG levels in aged and/or infertile males [ 17 , 49 , 50 ]. Surprisingly, the majority of these studies, which also include other vertebrate species, observed an increase [ 51 , 52 , 53 , 54 , 55 ] rather than a decrease [ 23 ] in global DNA methylation. The DNA methylation change after 24 HPS can be explained in relation to the environmental changes that have occurred by the spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…The observation is consistent with numerous studies that put into context aberrant sperm quality parameters and changes in mCpG levels in aged and/or infertile males [ 17 , 49 , 50 ]. Surprisingly, the majority of these studies, which also include other vertebrate species, observed an increase [ 51 , 52 , 53 , 54 , 55 ] rather than a decrease [ 23 ] in global DNA methylation. The DNA methylation change after 24 HPS can be explained in relation to the environmental changes that have occurred by the spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, lower DNA methylation levels were observed on Maternally Expressed Gene 3 (MEG3) and Necdin (NDN), but higher levels on the H19 gene 33 . A recent study shows that paternal aging can impact on the fertilization rate and day 5 embryo quality and that is preceded by deregulated methylation at imprinted genes in sperm 34 . Interestingly, the methylation status of sperm is dynamic and under environmental pressure.…”
Section: Discussionmentioning
confidence: 99%
“… 33 A recent study shows that paternal aging can impact on the fertilization rate and day 5 embryo quality and that is preceded by deregulated methylation at imprinted genes in sperm. 34 Interestingly, the methylation status of sperm is dynamic and under environmental pressure. More than 1500 unique genes had altered sperm DNA methylation profiles in six men undergoing Roux‐en‐Y gastric bypass surgery already 1 week after the surgery, which remained until at least 1 year after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is a reversible epigenetic mark and its effects may be reversed by using either demethylating agents, like DNA methyltransferase (DNMT) inhibitors, 5-azacitidine, and 5-aza-20 -deoxycytidine, or methyl donors, like choline, methionine, and folate [85,86]. However, a new study suggest that sperm methylation is a possible mechanism of age-induced poor reproductive outcomes among couples undergoing infertility treatment and that it can be used to identify the possible candidate genes for mediating the effects [87]. On the other hand, sperm cells from Norwegian red bulls of inferior fertility have less compact chromatin structure, higher levels of DNA damage, and are hypermethylated compared with bulls of superior fertility [88].…”
Section: Aberrant Sperm's Dna Methylation Patternsmentioning
confidence: 99%